Epigenetic Therapies in Melanoma—Targeting DNA Methylation and Histone Modification - Adrian Bogdan Tigu; Andrei Ivancuta; Andrada Uhl; Alexandru Cristian Sabo; Madalina Nistor; Ximena-Maria Mureșan; Diana Cenariu; Tanase Timis; Doru Diculescu; Diana Gulei (Biomedicines)
Skin cancer prevalence has increased during the last decades, with the last years serving as a pivotal moment for comprehending its epidemiological patterns and its impact on public health. Melanoma is one of the most frequently occurring malignancies, arising from a complex interplay of genetic factors, environmental factors, lifestyle and socio-economic conditions. Epigenetic changes play a critical role in tumor development, influencing progression and aggressiveness. Epigenetic therapies could represent novel therapeutic options, while drug repositioning may serve as a viable strategy for cancer treatment. Demethylating agents, commonly used in hematological malignancies, show promising results on solid tumors, including melanoma. Methylation patterns are responsible for tumor development by modulating gene expression, while histone acetylation influences DNA processes such as transcription, replication, repair, and recombination. This review aims to identify existing potential therapeutical approaches using therapeutic agents that can modulate DNA methylation and histone modification, which can lead to tumor inhibition, cell death initiation and reactivation of tumor suppressor genes.